HUBUNGAN PENGETAHUAN, SIKAP, DAN PERILAKU PASIEN HUMAN IMMUNODEFICIENY VIRUS DENGAN PELAYANAN VOLUNTARY COUNSELING AND TESTING DI RSUD DEPOK 2020 - Saraswati, Anisa Azhaar; Koesomo, Gatot Soeryo; Nugrohowati, Nunuk (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2021)
Human Immunodeficiency Virus (HIV) had become global emergency problem. The number of HIV cases in Indonesia reported until 2017 had increased, while the number of acquired immune deficiency syndrome (AIDS) cases was relatively stable. This prevalence showed that the more HIV status were known at early stage, the possibility of worsening could be reduced. Voluntary counseling and testing (VCT) is an HIV testing and counseling service that is implemented at the initiative of the patients. Good knowledge of HIV and positive attitude towards HIV will increase the initiative to take HIV test, supported by awareness of HIV risk behaviors.  The purpose of this study was to determine the relationship between knowledge, attitude, and behavior of PLHIV with the utilization of VCT services and to determine the most influencing factor of VCT service utilization. This study was an analytic observational cross-sectional design. The research samples were from a primary data which were questionnaires filled out by 43 HIV patients. The study was conducted at Depok Regional Public Hospital, the selection of this particular hospital was due to the high prevalence of HIV case in Depok. The sampling technique was consecutive sampling. This study proved that there was a significant relationship between knowledge (p-value: 0.008) and attitude (p-value: 0.000) with the utilization of VCT services. The utilization of VCT services increased with good knowledge of HIV and positive attitude towards HIV disease. Keywords: Attitude towards HIV; HIV risk behavior; Knowledge of HIV; Voluntary counseling and testin. AbstrakPenyakit Human Immunodeficiency Virus (HIV) telah menjadi masalah darurat global. Jumlah kasus HIV di Indonesia hingga tahun 2017 mengalami kenaikan, sedangkan jumlah acquired immune deficiency syndrome (AIDS) stabil. Prevalensi ini menunjukkan banyak orang dengan HIV/AIDS (ODHA) yang diketahui statusnya secara dini sehingga perburukan penyakit dapat dicegah. Voluntary counseling and testing (VCT) adalah layanan konseling dan tes HIV yang pelaksanaannya atas inisiatif pasien. Pengetahuan baik mengenai penyakit HIV dan sikap positif terhadap penyakit HIV akan meningkatkan inisiatif melakukan tes HIV, didukung oleh kesadaran perilaku berisiko terinfeksi HIV. Penelitian ini bertujuan mengetahui hubungan antara pengetahuan, sikap, dan perilaku pasien HIV/AIDS dengan pemanfaatan pelayanan VCT serta mengetahui faktor yang paling berpengaruh terhadap pemanfaatan pelayanan VCT. Penelitian ini bersifat analitik observasional dengan desain cross-sectional. Sampel penelitian berupa data primer yaitu pengisian kuesioner oleh 43 pasien HIV. Penelitian dilakukan di RSUD Depok, pemilihan di RSUD Depok karena tingginya prevalensi penyakit HIV di Depok. Teknik pengambilan sampel pada penelitian ini secara consecutive sampling. Penelitian ini membuktikan terdapat hubungan bermakna antara pengetahuan (p-value: 0.008) dan sikap (p-value: 0.000) terhadap pemanfaatan pelayanan VCT. Pemanfaatan pelayanan VCT meningkat dengan pengetahuan baik mengenai HIV dan sikap positif terhadap penyakit HIV.